2020
DOI: 10.1371/journal.pone.0226258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of the age-period-birth cohort on cervical cancer mortality in the Brazilian Northeast

Abstract: Cervical cancer (CC) is a public health problem with a high disease burden and mortality in developing countries. In Brazil, areas with low human development index have the highest incidence rates of Brazil and upward temporal trend for this disease. The Northeast region has the second highest incidence of cervical cancer (20.47 new cases / 100,000 women). In this region, the mortality rates are similar to rates in countries that do not have a health system with a universal access screening program, as in Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 55 publications
6
29
0
3
Order By: Relevance
“…The greater access to health care services and socioeconomic income of the population in this region further explains the findings of this study [ 3 , 7 ]. Similarly, studies in Brazil and the United States reported a lower mortality rates in states with both higher human development indexes and economic incomes [ 38 , 39 ]. Nevertheless, it is to be expected that rapid access to healthcare facilities and the availability of therapy would result in lower mortality trends in the coastal region.…”
Section: Discussionmentioning
confidence: 91%
“…The greater access to health care services and socioeconomic income of the population in this region further explains the findings of this study [ 3 , 7 ]. Similarly, studies in Brazil and the United States reported a lower mortality rates in states with both higher human development indexes and economic incomes [ 38 , 39 ]. Nevertheless, it is to be expected that rapid access to healthcare facilities and the availability of therapy would result in lower mortality trends in the coastal region.…”
Section: Discussionmentioning
confidence: 91%
“…Res. Public Health 2021, 18, 5607 2 of 11 factors influencing disease incidence and mortality [8]. Considering that previous studies in China possibly ignored the interaction between age, period and cohort effects [9,10], we used an age-period-cohort (APC) model to simultaneously calculate these three variables [11].…”
Section: Introductionmentioning
confidence: 99%
“…This study also aimed to estimate age, period and cohort effects on TB notification and mortality in mainland Chinese residents. Age, period and cohort are usually three key factors influencing disease incidence and mortality [ 8 ]. Considering that previous studies in China possibly ignored the interaction between age, period and cohort effects [ 9 , 10 ], we used an age–period–cohort (APC) model to simultaneously calculate these three variables [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of death was estimated by relative risk (RR) estimates and 95% confidence intervals according to period and cohort effects. Estimates for the Age Period and Cohort models were made using the Epi library 1.1.18 (R Foundation of Computational Statistics, Vienna, Austria http://www.r-project.org) of the R program (version 4.1) [25].…”
Section: Discussionmentioning
confidence: 99%